The influence of principal instructional leadership practices on teachers’ self-efficacy at an International Baccalaureate School / Nurini Fazilawati Shaharuddin. - Shaharuddin, Nurini Fazilawati (2016)
Principal instructional leadership influences teachers’ confidence in their ability to conduct teaching and learning processes. However, previous studies showed that principal instructional leadership practices that influence teachers’ self-efficacy are not given enough attention in the settings of international school. This study intended to investigate principal instructional leadership practices and teachers’ self-efficacy at an international school that offers the International Baccalaureate programmes. The study used a mixed-methods design which involves both quantitative and qualitative methods. The quantitative method involved 50 teachers, while the qualitative method involved four teachers from international school in Klang Valley. A questionnaire combining two scales namely Principal Instructional Management Rating Scale by Hallinger (1990), and Teacher Self Efficacy Scale by Tshannen-Moran and Hoy (2001) was used to obtain quantitative data. While, for qualitative method, the interview protocol was developed and validated by experts in this field. Result of the study revealed both principal instructional leadership practices and teachers’ self-efficacy were at moderate levels. The findings also suggest that there is no significant relationship between principal instructional leadership practices and teachers’ self-efficacy at IB School. Various implications were derived from the findings including contributes to the literature in leadership and psychology fields, provide an insight view to the private school principal to improve their instructional leadership skills and the related departments to develop a training programs for principals and teachers. The researcher also recommends that principal instructional leadership programs be developed, to enhance teachers’ self-efficacy through continuous professional development programs and employment of a counselor for teachers.